2007
DOI: 10.1902/jop.2007.060217
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Crevicular Fluid Prostaglandin E2 and Thiobarbituric Acid Reactive Substance Levels in Smokers and Non‐Smokers With Chronic Periodontitis Following Phase I Periodontal Therapy and Adjunctive Use of Flurbiprofen

Abstract: These results suggest that additional flurbiprofen administration may have more inhibitory effects on GCF levels of PGE(2) and TBARS in the groups of smokers compared to non-smokers with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…The present study has observed that smokers with chronic periodontitis showed lower GI and PBI and higher PI and CAL as compared to non-smokers with chronic periodontitis. In accordance with our study, various studies [22][23][24] have observed altered clinical parameters in smokers with chronic periodontitis compared to non-smokers.…”
Section: Discussionsupporting
confidence: 93%
“…The present study has observed that smokers with chronic periodontitis showed lower GI and PBI and higher PI and CAL as compared to non-smokers with chronic periodontitis. In accordance with our study, various studies [22][23][24] have observed altered clinical parameters in smokers with chronic periodontitis compared to non-smokers.…”
Section: Discussionsupporting
confidence: 93%
“…The last product of the lipid peroxidation process, malondialdehyde (MDA), is a frequently used parameter in measuring the oxidative damage to the lipids resulting from free radicals [39]. Thiobarbituric acid reactive substances test (TBARS) is the most widely used test in the measurement of MDA levels [40, 41]. Some previous studies have shown that serum levels of MDA were increased in systemic diseases such as tuberculosis and that salivary levels of MDA were also significantly increased in periodontal diseases and reported that this increase in MDA levels is an important indicator of periodontal tissue destruction [38].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Tomasi and Wennström 35 reported additional benefits with the use of adjunctive local doxycycline in the treatment of smokers. Also, we should mention our previous investigation of the effects of SRP and the adjunctive use of flurbiprofen on the GCF PGE 2 and thiobarbituric acid reactive substance (TBARS) levels in smokers and non‐smokers with CP 36 . SRP plus flurbiprofen had more inhibitory effects on GCF levels of PGE 2 and TBARS in smokers compared to non‐smokers with CP.…”
mentioning
confidence: 92%